2013
DOI: 10.1016/j.lfs.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine lysolipids in the CNS: Endogenous cannabinoid antagonists or a parallel pain modulatory system?

Abstract: A significant number of patients experience chronic pain and the intractable side effects of currently prescribed pain medications. Recent evidence indicates important pain modulatory roles for two classes of G-protein-coupled receptors that are activated by endogenous lipid ligands, the endocannabinoid (eCB) and sphingosine-1-phosphate (S1P) receptors, which are widely expressed in both the immune and nervous systems. In the central nervous system (CNS), CB1 cannabinoid and S1P1 receptors are most abundantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…In mouse, thymic levels of the bioactive phospholipid S1P vary in parallel to that of P‐selectin , and S1P regulates lymphocyte trafficking as well as HSC mobilization similarly to CNR2 . CB‐ and S1P‐signaling interact at multiple levels: AEA increases S1P phosphorylation , and CNR1‐stimulation enhances ceramide biosynthesis, the substrate for S1P ; further, sphingosine can bind to CNR1 as an antagonist , suggesting potential feedback regulation. It will be interesting to determine if just as CNR2‐signaling modulates AGM HSCs through cross‐regulatory effects on PGE2; CHT and thymus colonization occurs via regulation of S1P or other lipid mediators.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse, thymic levels of the bioactive phospholipid S1P vary in parallel to that of P‐selectin , and S1P regulates lymphocyte trafficking as well as HSC mobilization similarly to CNR2 . CB‐ and S1P‐signaling interact at multiple levels: AEA increases S1P phosphorylation , and CNR1‐stimulation enhances ceramide biosynthesis, the substrate for S1P ; further, sphingosine can bind to CNR1 as an antagonist , suggesting potential feedback regulation. It will be interesting to determine if just as CNR2‐signaling modulates AGM HSCs through cross‐regulatory effects on PGE2; CHT and thymus colonization occurs via regulation of S1P or other lipid mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations of elevated lysoGb3 with pain have been earlier observed [46] and more recently experimental evidence has been presented directly implicating lysoGb3 in the damage of nociceptive neurons [47]. Of note, S1P acting peripherally at S1P1 and S1P3 receptors can enhance sensitivity to various pain stimuli or elicit spontaneous pain [48], S1P can also act as antagonists of CB1 cannabinoid receptors involved in pain suppression [48]. In addition, S1P has recently been reported to stimulate excitatory transmission in neurons [13].…”
Section: Discussionmentioning
confidence: 92%
“…These effects appeared to be CB1 receptorindependent. Recently, regarding pain modulation, the same research group suggested probable points of interaction between the cannabinoids and endogenous sphingolipid systems [163].…”
Section: S1p Fingolimod and Epilepsymentioning
confidence: 99%